Verbal fluency tests: Normative data for Spanish-speaking pediatric population - Olabarrieta-Landa, L; Rivera, D; Lara, L; Rute-Pérez, Sandra; Rodríguez-Lorenzana, A; Galarza-del-Ángel, J; Peñalver Guia, A I; Ferrer-Cascales, R; Velázquez-Cardoso, J; Campos Varillas, A I; Ramos-Usuga, D; Chino-Vilca, B; et al. (NeuroRehabilitation, 2017)
OBJECTIVE: To generate normative data for the Verbal Fluency Tests across 11 countries in Latin America, with country-specific adjustments for gender, age, and education, where appropriate. METHOD: The sample consisted of 3,977 healthy adults who were recruited from Argentina, Bolivia, Chile, Cuba, El Salvador, Guatemala, Honduras, Mexico, Paraguay, Peru, and, Puerto Rico. Each subject was administered the Verbal Fluency Test as part of a larger neuropsychological battery. A standardized five-step statistical procedure was used to generate the norms. RESULTS: The final multiple linear regression models for the letter F explained 8-30% of the variance, 7-32% for letter A, 8-32% for the letter S, and 16-43% for the animal category in Verbal Fluency Test scores. Although t-tests showed significant differences between men and women on the Verbal Fluency Test, they did not have an effect size larger than 0.3. As a result, gender-adjusted norms were not generated. CONCLUSIONS: This is the first normative multicenter study conducted in Latin America aiming to create norms for the Verbal Fluency Test; this study will have important outcomes for the future of neuropsychology in the region.
Keywords: Latin America; Normative data; executive functions; phonological verbal fluency test; semantic verbal fluency test; JCR; Scopus